Promotion of Healthy Habits in Adolescents: An Interdisciplinary Study on Motivation Towards Physical Education, Mediterranean Diet and Physical Activity - Paula San Martín González; José Enrique Moral García; Mario Amatria Jiménez; Rubén Arroyo del Bosque (Behavioral Sciences)
Adolescence is a key period for the development and consolidation of habits that favour a healthy and active lifestyle. The promotion of healthy habits in this critical period of development is essential to ensure a better quality of life and the prevention of chronic diseases in the long term. This study aims to analyse how physical activity (PA) and adherence to the Mediterranean diet (MD) influence motivation towards physical education (PE) in adolescents. It also aims to explore gender differences and provide information that will allow the design of educational strategies to promote healthy lifestyle habits in schools. Method: descriptive cross-sectional quantitative study. An ad hoc socio-demographic questionnaire, the Physician-based Assessment and Counselling for Exercise, the KIDMED Mediterranean diet adherence questionnaire and the motivation in Physical Education questionnaire were administered in the school environment under direct supervision of the researchers to minimise biases in self-perception. Results: Students with higher adherence to the Mediterranean diet showed higher intrinsic motivation towards physical education (F = 5.133, p < 0.01), while those with lower adherence showed higher demotivation (F = 5.507, p < 0.01). Conclusions: The findings suggest the need to reinforce physical activity and nutrition education programmes in adolescents, promoting interdisciplinary approaches to increase adherence to healthy lifestyles.